From Bloom's Taxonomy Into Webb's Depth of Knowledge: Enhancing Lesson Planning Strategies - Masharipova, Feruza (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article examines the shift from Bloom’s Taxonomy, a well-established model of cognitive skills, to Webb’s Depth of Knowledge (DOK), which focuses on the complexity of cognitive tasks. It provides an overview of both frameworks and discusses their roles in lesson planning and instructional design. While Bloom’s Taxonomy serves as a foundational tool for structuring learning objectives across levels of understanding, application, and creation, Webb’s DOK offers a more nuanced approach by emphasizing the depth of student engagement and cognitive rigor. Combined, these frameworks form a robust strategy for designing lessons that promote critical thinking and adaptability. By integrating Bloom’s Taxonomy with Webb’s DOK, educators can better align instructional goals with student outcomes, creating a progressive and comprehensive learning experience. This article also presents strategies for incorporating both frameworks into lesson planning, offering practical insights and examples for educators seeking to enhance student autonomy and engagement.